Widely tunable erbium-doped fiber laser based on multimode interference effect - Castillo Guzmán, Arturo Alberto; Antonio Lopez, J. E.; Selvas Aguilar, Romeo; May Arrioja, D. A.; Estudillo Ayala, Julián Moisés (2010)
A widely tunable erbium-doped all-fiber laser has been demonstrated. The tunable mechanism is based on a novel tunable filter using multimode interference effects (MMI). The tunable MMI filter was applied to fabricate a tunable erbium-doped fiber laser via a standard ring cavity. A tuning range of 60 nm was obtained, ranging from 1549 nm to 1609 nm, with a signal to noise ratio of 40 dB. The tunable MMI filter mechanism is very simple and inexpensive, but also quite efficient as a wavelength tunable filter.